Meningkatkan Hasil Belajar Siswa dalam Pembelajaran IPA pada Konsep Pesawat Sederhana melalui Pendekatan Inkuiri Di Smp Negeri 2 Telukjambe Barat - Dewi, Sri Ratna (Attractive : Innovative Education Journal, 2024)
Learning Natural Sciences (Science) requires an interesting and interactive approach so that students can understand scientific concepts thoroughly. One concept that is often a challenge is a simple aircraft. This research aims to improve student learning outcomes in science learning on simple airplane concepts through an inquiry approach at SMP Negeri 2 Telukjambe Barat, class VIII B. The method used in this research is classroom action research (CAR) using an inquiry approach as a learning method. Research was carried out in several cycles involving observation, reflection and continuous improvement actions. The instruments used to collect data are tests, observations and field notes. The research results show a significant increase in student learning outcomes after implementing the inquiry approach. Students show increased understanding of simple airplane concepts, critical thinking skills, and interest in learning material. In addition, student participation in the learning process also increased, showing the effectiveness of the inquiry approach in motivating students to learn actively. Keywords: Learning Outcomes, Inquiry Approach, Science Learning